2011
DOI: 10.4050/jahs.56.022005
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Optimization of MAV-Scale Cycloidal Rotor Performance

Abstract: This paper describes the systematic experimental studies performed to optimize the performance of a microscale cycloidal rotor. Parametric studies were conducted to determine the dependence of cycloidal rotor performance on rotational speed, blade pitching amplitude (symmetric and asymmetric pitching), blade airfoil profile, number of blades (at constant solidity), and the location of pitching axis. Higher blade pitch angles were found to improve the power loading (thrust/power) of the cycloidal rotor. Asymmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…[15]. Previous studies performed at the University of Maryland [10,[15][16][17][18][19][20] included systematic experimental studies on a micro-scale cycloidal rotor with rotor dimensions of approximately 6 inches (0.152 meters) in diameter and span. A wide range of kinematic and geometric parameters were systematically varied to study their impact on rotor performance in hover.…”
Section: Introductionmentioning
confidence: 99%
“…[15]. Previous studies performed at the University of Maryland [10,[15][16][17][18][19][20] included systematic experimental studies on a micro-scale cycloidal rotor with rotor dimensions of approximately 6 inches (0.152 meters) in diameter and span. A wide range of kinematic and geometric parameters were systematically varied to study their impact on rotor performance in hover.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13]. The understanding gained from these studies was used to design the cyclorotor used on the Twincyclo.…”
Section: Rotor Performancementioning
confidence: 99%
“…Previous studies at the University of Maryland have shown that the cyclorotors, if systematically optimized, can reach aerodynamic efficiencies higher than conventional rotor systems (Refs. [10][11][12][13][14]. Figure 3 shows that the power loading (thrust/power) of an optimized cyclorotor is higher than that of a conventional microrotor of similar actuator area (diameter = 9 inches, solidity = 0.137) at the same disk loading (Ref.…”
Section: Introductionmentioning
confidence: 99%
“…5,(12)(13)(14). The rotor consisted of a span and diameter of approximately 15 cm, and the effects of blade kinematics and rotor geometry on hover performance were examined through a wide range of parameters.…”
Section: Introductionmentioning
confidence: 99%